A palynological survey of the genus Scrophularia L. (Scrophulariaceae) from Turkey. Issue 3 (4th May 2022) - Özbek, Funda; Pinar, Nur Münevver; Uzunhİsarcikli, Mehmet Erkan; Ekİcİ, Murat
Abstract: Pollen morphology of 73 taxa belonging to the genus Scrophularia L. (Scrophulariaceae) distributed in Turkey is examined with light microscopy (LM) and scanning electron microscopy (SEM) to determine their properties and assess their taxonomic significance. The pollen grains of Scrophularia are radially symmetrical and isopolar. Their shape is oblate-spheroidal, suboblate, and prolate-spheroidal, with the polar axis ranging from 16.56 µm to 32.88 µm and the equatorial axis ranging from 18.24 µm to 35.52 µm. The aperture type is usually trizonocolporate but is rarely tetracolporate and trisyncolporate. Four types of exine ornamentation are observed: microreticulate, reticulate, microreticulate-rugulate, and suprareticulate. Numerical analysis reveals that pollen dimensions and exine sculpturing are the most useful diagnostic variables for discriminating Scrophularia taxa. Results also show a partial relationship between the Scrophularia taxa clustered on the basis of pollen morphology and the systematics of these taxa on the basis of general macromorphology.